IT Shields : Technology Adoption and Economic Resilience during the COVID-19 Pandemic - Pierri, Nicola (IMF Working Papers; Working Paper ;, 2020)
We study the economic effects of information technology (IT) adoption during the COVID-19 pandemic. Using data on IT adoption covering almost three million establishments in the US, we find that technology adoption can partly shield the economy from the impact of the pandemic. In areas where firms adopted more IT the unemployment rate rose less in response to social distancing. Our estimates imply that if the pandemic had hit the world 5 years ago, the resulting unemployment rate would have been 2 percentage points higher during April and May 2020 (16% vs. 14%), due to the lower availability of IT. Local IT adop-tion mitigates the labor market consequences of the pandemic for all individuals, regardless of gender and race, except those with the lowest level of educational attainment.